Hubungan Resiliensi dengan Burnout pada Petani Padi di Desa Ampel, Wuluhan - Muhammad Anshori Rizqi Putra; Erti Ikhtiarini Dewi Dewi; Enggal Hadi Kurniyawan (Pustaka Kesehatan, 2021)
Problems caused by burnout are very dangerous for workers, namely work stress that continues to increase, performance continues to decline and can even make workers experience physical and psychological disorders. Farmers must have positive thoughts about any problems they face by having the nature of resilience. The purpose of this study was to determine the relationship between resilience and burnout on rice farmers in Ampel village, Wuluhan district. This study used a cross sectional design with sampling techniques using cluster random sampling with a sample of 80 rice farmers. Data retrieval was done by resilience scale-14 questionnaire and MBI-GS questionnaire. The results of this study indicate that the resistance experienced by farmers is 100% high, while burnout is obtained which is 55% low and 45% high. The results of bivariate analysis with the Pearson correlation obtained a p-value = 0,003 which means there is relationship between resilience and burnout on rice farmers in Ampel Village, Wuluhan district. The research results can be used as an evaluation especially for health services to be more care for rice farmers so they can improve health.